THERMOELASTIC PROPERTIES OF ROCK-FORMING MINERALS - Prodaivoda G.T.; Maslov B.P.; Prodaivoda T.G. (My University, 2004)
The thermoelastic moduli of rock-forming minerals and their derivatives are estimated using inversion of pressure- and temperature-dependent P and S velocities. The elastic constants obtained by the new method are tested against averaged experimental Voigt-Reuss-Hill elastic constants.